Persepsi Guru Tentang Kinerja Kepemimpinan Kepala Sekolah Dalam Pengelolaan Pendidikan Di SMA Negeri 3 Halmahera Barat - Asnita Ode Samili; Fitriana Ibrahim; Syarifuddin Adjam; Jainudin Hasim (Jurnal Ilmiah Wahana Pendidikan, 2023)
This study aims to determine teachers' perceptions of the principal's leadership performance. This research uses a descriptive qualitative method with a case study approach. Sources of data in this study are teachers and principals. Data collection techniques using interview techniques, observation, and documentation. Data analysis uses a path analysis model to analyze qualitative data through the steps of data collection, data reduction, data presentation, and verification or drawing conclusions. The results of this study indicate that teachers have a positive perception of the principal's leadership in terms of leadership in school or learning, managerial leadership, and organizational leadership. So that the wheels of leadership run well as evidenced by good academic achievements, student achievements, and teacher achievements in developing the quality of learning.